NGHIÊN CỨU HOẠT TÍNH CỦA RÂY PHÂN TỬ ALPO-5 CHỨA SẮT TRONG PHẢN ỨNG OXI HÓA FENTON DỊ THỂ PHENOL PHẦN I - ẢNH HƯỞNG CỦA CÁC PHƯƠNG PHÁP CHẾ TẠO ĐẾN HOẠT TÍNH XÚC TÁC CỦA CÁC RÂY PHÂN TỬ ALPO-5 CHỨA SẮT - Nhiên, Phạm Quốc; Huy, Đỗ Mạnh; Dung, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
In this study, the FeAlPO-5, Fe/AlPO-5 and FexOy/AlPO-5 molecular sieves were prepared by hydrothermal, impregnation and precipitation methods, respectively. The molecular sieves were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance UV-VIS spectroscopy (DR UV-Vis) techniques and Scanning electron microscopy (SEM) and evaluated in the Fenton oxidation of phenol. The results reveal that iron in the FexOy/AlPO-5 molecular sieve mainly exists in iron oxide and hydroxide forms. The amount of iron oxide in the molecular sieves increases in the order of FeAlPO-5 < Fe/AlPO-5 < FexOy/AlPO-5 and the catalytic activities of the Fe containing AlPO-5 molecular sieves also increase in this order.